A thermodynamic comparison between organic Rankine and Kalina cycles for waste heat recovery from the Gas Turbine-Modular Helium Reactor. (1st January 2015) - Zare, V.; Mahmoudi, S.M.S.
Abstract: A comparative thermodynamic analysis and optimization is presented for waste heat recovery from the Gas Turbine-Modular Helium Reactor (GT-MHR) employing organic Rankine cycle (ORC) and Kalina cycle (KC). Thermodynamic models are developed for the stand alone GT-MHR and the two proposed combined cycles and the effects on the performances of the cycles are investigated of decision variables. The cycles' performances are then optimized based on the first and second law of thermodynamics. The results showed that, employing ORC is more appropriate than KC for GT-MHR waste heat recovery. The first and second law efficiencies of the combined GT-MHR/ORC are higher than those of the combined GT-MHR/KC. In addition, the helium mass flow rate in the combined GT-MHR/ORC is significantly lower than that in the combined GT-MHR/KC. Moreover, the high-pressure level of the ORC is extremely lower than that of the KC under optimized conditions. Furthermore, the superheated vapor at the ORC turbine exit avoids droplet erosion and allows for reliable operation while the stream exiting the KC turbine is a two-phase flow. Highlights: Organic Rankine cycle performs better than Kalina cycle for GT-MHR waste heat recovery. GT-MHR efficiency is enhanced by 11.3% when it is combined with the ORC. Superheating at bottoming cycles' turbine inlet decreases the combined cycle efficiency.